Perancangan Pakaian Siap Pakai Dengan Kombinasi Teknik Melukis Diatas Air Dan Eco Print - Angdawuni, Nabila Azzahra; Sarwono, Sarwono (Universitas Negeri Surabaya, 2024)
Industry players are required to be more creative and innovative in developing textile products with various manufacturing techniques. The development of textile products that did not produce textile waste and did not adversely affect the environment to make ready-made clothing for women. The purpose of this design is an update in the combination of Painting on Water and Eco Print techniques, which is for the development of textile products that do not produce textile waste if produced into ready-made clothing. The method used in the creation of artwork according to SP. Gustami. The result of three stages of creation analysis is the observation of Eco Print Ramban Ayu in Temanggung and Painting On Air Mangsi Kelir which originated in Bandung, the design by creating various combinations of designs from both techniques, and the embodiment of being used as ready-made clothing for female teenagers. The results of the design resulted in motif design and ready-made fashion design. With Painting Techniques on Water as the basis of dyeing and Eco Print as the main motif. The design resulted in the design being realized as a ready-to-use fashion product for female teenagers aged 15 to 23 using the color palette trend 2023.